2016
DOI: 10.1515/aep-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

Operation mode and external carbon dose as determining factors in elemental composition and morphology of aerobic granules

Abstract: Abstract:The elemental composition and morphology of aerobic granules in sequencing batch reactors (GSBRs) treating high-nitrogen digester supernatant was investigated. The investigation particularly focused on the effect of the number of anoxic phases (one vs. two) in the cycle and the dose of external organics loading (450 mg COD/(L·cycle) vs. 540 mg COD/(L·cycle)) on granule characteristics.Granules in all reactors were formed of many single cells of rod and spherical bacteria. Addition of the second anoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Ca-rich granules have higher mechanical strength but lower bioactivity, so the calcium ion content of aerobic granules is one of the factors determining their bioactivity. The granulation time and stimulation of cell-to-cell aggregation can be reduced by calcium-induced dehydration of bacterial cell surfaces [ 43 , 44 , 45 ]. In the present study, the concentration of calcium ions in the raw wastewater was 0.27 mmol Ca/L.…”
Section: Resultsmentioning
confidence: 99%
“…Ca-rich granules have higher mechanical strength but lower bioactivity, so the calcium ion content of aerobic granules is one of the factors determining their bioactivity. The granulation time and stimulation of cell-to-cell aggregation can be reduced by calcium-induced dehydration of bacterial cell surfaces [ 43 , 44 , 45 ]. In the present study, the concentration of calcium ions in the raw wastewater was 0.27 mmol Ca/L.…”
Section: Resultsmentioning
confidence: 99%
“…The content of calcium ions is a factor determining the aerobic bioactivity of granules, given the way these ions can induce dehydration at the surface of bacterial cells. This stimulates the aggregation of microorganisms and shortens the biogranulation time [42,48]. In the research presented here, the concentration of the calcium cation in raw wastewater was 0.27 mmol Ca/L.…”
Section: Biological Properties Of Biomassmentioning
confidence: 87%
“…In the reactors with PK and PL, the Ca/P ratio was below 1. Cydzik-Kwiatkowska et al [42] reported that the dose of the external carbon source is a decisive factor affecting the elemental composition of biomass. The granules cultured at a dose of 540 mg COD/(L•cycle) had a higher percentage by weight of C, S and N, which indicated the presence of greater amounts of organic compounds in the structure of the granular sludge.…”
Section: Selected Chemical Properties Of Biomassmentioning
confidence: 99%
“…The dried samples were gold coated in an argon atmosphere using an ion coater (Fine Coater, JCF-1200, JEOL, Akishima, Japan). The samples were imaged using an SEM (JSM-5310LV, JEOL, Akishima, Japan) at 15 kV [39].…”
Section: Methodsmentioning
confidence: 99%